Evaluation of diagnostic accuracy of intracranial aneurysm detection using medical-grade versus commercial consumer-grade displays and different image reconstructions against the background of process optimization for telemedicine. (July 2020) - Auer, Timo Alexander; Münzfeld, Hanna; Posch, Helena; Stöckel, Juliane; Tietze, Anna; Bohner, Georg; Böning, Georg
Background: Process optimization in computed tomography (CT) and telemedicine. Purpose: To compare image quality and objective diagnostic accuracy of medical-grade and consumer-grade digital displays/computer terminals for detection of intracranial aneurysms. Material and Methods: Four radiologists with different levels of experience retrospectively read a total of 60 patients including 30 cases of proven therapy-naïve intracranial aneurysm detectable on a medical-grade grayscale calibrated display. They had 5 min per case reading the first 20 datasets using only axial slices, the next 20 patients using axial slices and multiplanar reconstructions (MPRs), and the last 20 patients using axial slices, MPRs, and maximum intensity projections (MIPs). Three months after the first reading session on a medical-grade display, they read all datasets again under the same standardized conditions but on a consumer-grade display. Diagnostic performance, subjective diagnostic confidence, and reading speed were analyzed and compared. Readers rated image quality on a five-point Likert scale. Results: Diagnostic accuracy did not differ significantly with areas under the curve of 0.717–0.809 for all readers on both display devices. Sensitivity and specificity did not increase significantly when adding MPRs and/or MIPs. Reading speed was similar with both devices. There were no significant differences in subjective image quality scores, and overall inter-reader variability of all subjective parameters correlated positively between the two devices ( P <0.001–0.011). Conclusion: Diagnostic accuracy and readers' diagnostic confidence in detecting and ruling out intracranial aneurysm were similar on commercial-grade and medical-grade displays. Additional reconstructions did not increase sensitivity/specificity or reduce the time needed for diagnosis.